A fuzzy inventory model for deteriorating items with stock dependent demand rate. Issue 4 (2018) - Indrajitsingha, S.K.; Samanta, P.N.; Misra, U.K.
The present paper proposes a fuzzy economic order quantity (EOQ) model for deteriorating items with stock dependent demand rate where shortages are not allowed. The cycle time is divided into two parts. The first interval demand is considered as stock dependent and the second part is assumed to be constant. We first develop a crisp model. Since most of the parameters of the inventory model are uncertain, we consider the demand, holding cost, deterioration cost and deterioration rate as triangular fuzzy numbers. Graded mean representation, signed distance method and centroid method are used to defuzzify the total cost function. The results obtained by these methods are compared with the help of a numerical example. Sensitivity analysis is also carried out to explore the effect of changes in the values of the system parameters.